EFFECTS OF DIGITAL CAREER EXPLORATION AND CAREER SELF-EFFICACY ON SENIOR HIGH SCHOOL STUDENTS’ CAREER MATURITY - Queendra Cheryl Wibowo; Denok Setiawati; Budi Purwoko; Evi Winingsih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research seeks to analyze the effect of digital career exploration and career self-efficacy on the career maturity of senior high school students. The study adopted a quantitative method with an explanatory research design and involved 80 eleventh-grade students from SMA Negeri 13 Surabaya, who were selected using a simple random sampling technique. Data collection was conducted through an online questionnaire, which had previously undergone validity and reliability testing. Multiple linear regression analysis was used to test the partial and simultaneous effects among variables. The findings reveal that digital career exploration significantly and positively influences career maturity. This indicates that students who utilize digital platforms to access career-related information tend to have a clearer understanding of career options and demonstrate greater readiness in making career decisions. In addition, career self-efficacy was also found to have a positive and stronger effect on career maturity. This result emphasizes that individuals’ belief in their capacity to plan career paths, make appropriate choices, and manage career-related obstacles plays a vital role in the development of career maturity. Simultaneously, both variables explain 76% of the variance in career maturity. These findings further underline the need to enhance digital career exploration and career self-efficacy through the implementation of effective career guidance programs in schools.